Assessment of Accuracy the Nonlinear Static Analysis in Determining Behavior Factor Reinforced Concrete Moment-Resisiting Frames - Alireza Habibi (Iranian Society of Structrual Engineering (ISSE), 2015)
Common methods analysis and design of structures are based according to elastic analysis and and reduction of earthquake forces. This reduction design load in the codes is done by the behavior factors. Applying the non-linear static analysis and make ideals pushover curves obtained from its, including conventional in determining behavior factor. The purpose of this study is evaluating the accuracy of nonlinear static analysis in determining behavior factor reinforced concrete moment-resisiting framesby performing nonlinear incremental dynamic analysis that is a more accurate analysisby considering the damping, dynamic nature of the load and higher modes effects. The response modiﬁcation factors for reinforced concrete moment-resisiting framesobtained in this study by performing nonlinear incremental dynamic analysis  are difference about %13 those obtained by pushover analyses analysis. The results of nonlinear incremental dynamic analysis are generally more than those obtained from pushover analysis.